2022
DOI: 10.3390/insects14010002
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Entomopathogenic Nematode HbSD as a Candidate Biocontrol Agent against Spodoptera frugiperda

Abstract: Spodoptera frugiperda is a highly destructive and polyphagous pest that causes severe damage to various crops, especially maize. The wide use of chemical insecticides to control S. frugiperda results in resistance against commonly used chemicals and resistant mutations will expand in populations accompanied by a spread to vulnerable areas. Consequently, more effective and friendly strategies must be explored to minimize losses caused by S. frugiperda. Entomopathogenic nematodes (EPN) are good candidates for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The fall armyworm (FAW), Spodoptera frugiperda, is a widely adaptable pest that poses a significant threat to maize and various cereals in tropical and subtropical areas across the globe [1]. Originating from the Americas, recent incursion of the FAW into Africa, Asia, and Oceania has resulted in substantial reductions in yields of multiple food crops [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fall armyworm (FAW), Spodoptera frugiperda, is a widely adaptable pest that poses a significant threat to maize and various cereals in tropical and subtropical areas across the globe [1]. Originating from the Americas, recent incursion of the FAW into Africa, Asia, and Oceania has resulted in substantial reductions in yields of multiple food crops [2].…”
Section: Introductionmentioning
confidence: 99%
“…A prudent approach involves isolating entomopathogenic bacteria from infected insects and cultivating them to evaluate their insecticidal impact, either through cell cultures or the examination of potential secondary metabolites, such as toxins or enzymes. An example of employing bacterial cells against S. frugipedra is seen in a recent investigation conducted by Chen et al [1], who isolated entomopathogenic nematodes, specifically Heterorhabditis bacteriophora, demonstrating their effectiveness across laboratory, greenhouse, and field settings. Another example of utilizing secondary metabolites as insecticides is presented by Sun et al [2], where a fungal-derived Cyclosporin A demonstrated notable insecticidal efficacy (LC50 = 9.69 µg/g) against FAWs by effectively inhibiting calcineurin (CaN) activity, resulting in significant suppression of the pests.…”
Section: Introductionmentioning
confidence: 99%